Systemic Lupus Erythematosus Presenting With Bilateral Vertebral Artery Dissection: Case Report - (:unkn) unknown (AVES YAYINCILIK, IBRAHIM KARA, 2009)
Ischemic stroke due to cervicocranial artery dissections is a relatively common situation especially in the young population. Rarely it may present with intracranial hemorrhage rather than ischemia Systemic lupus erythematosus usually cause occlusive disease of large cerebral vessels by means of inflammatory vasculopathy and sometimes arterial dissection. A case presenting with both ischemia and subarachnoid hemorrhage due to bilateral vertebral artery dissection will be discussed in the present study.
Keywords: Dissection; stroke, subarachnoid hemorrhage, vertebral artery; systemic lupus erythematosus